Nutritional Status of Patients with Chronic Kidney Disease undergoing Hemodialysis - Marcet Franco, Igor Ernesto; Acosta González, Juan Daniel; Quintana, Claudia Patrícia; Ortigoza, Edis Emanuel; Barrios, Jazmín; Ríos Mujica, Patricia (Medicina Clínica y Social, 2025)
Introduction: Chronic kidney disease (CKD) is a major public health issue, with a global prevalence of nearly 13% and a growing burden in Latin America and Paraguay. In advanced stages, hemodialysis becomes indispensable but may negatively affect nutritional status, leading to both undernutrition and overweight. Nutritional assessment through indicators such as body mass index (BMI) and sociodemographic data is essential to understand these alterations and guide intervention strategies. Objective: To evaluate the nutritional status of patients undergoing hemodialysis in a private center in Asunción, Paraguay, using anthropometric measurements and sociodemographic data. Methodology: Observational, descriptive, cross-sectional study in 120 adult hemodialysis patients. Sociodemographic information and anthropometric measurements (weight, height, BMI) were collected. Descriptive statistics and association tests were applied. Results: The mean age was 57.2 ± 13.2 years, with a male predominance (56.7%). Mean BMI was 27.3 ± 5.3 kg/m². A high prevalence of overweight (40.8%) and obesity (28.4%) was observed, with no cases of undernutrition. No significant differences in BMI were found between sexes or age groups, although variations in weight and height were noted. Conclusion: Hemodialysis patients showed a high prevalence of overweight and obesity, challenging the traditional perception of undernutrition in this population. These findings highlight the need for personalized nutritional interventions that address the complex nutritional profile of CKD patients